Interfacial charge transfer processes in 2D and 3D semiconducting hybrid perovskites: azobenzene as photoswitchable ligand - Fillafer, Nicole; Seewald, Tobias; Schmidt-Mende, Lukas; Polarz, Sebastian (Beilstein Journal of Nanotechnology, 2020)
In the vast majority of studies on semiconductor particles ligands or capping agents are used that bind to the surface of the particles covering them with an electrically insulating shell. Since the transport of charge carriers and/or energy across interfaces is desirable for a variety of applications, the use of π-conjugated ligands becomes increasingly interesting. Among them are compounds that react to external stimuli. Molecular switches in particular are fascinating because the properties of the interfaces can be potentially adjusted as required. However, there is debate about how the properties of such special ligands are influenced by the presence of a semiconductor and vice versa. Here ammonium-modified azobenzene compounds were selected as prototypes for molecular switches and organic–inorganic hybrid perovskites as semiconductor materials. The class of ammonium–lead–halide phases as prototypes is peculiar because, in addition to the surface functionalization of 3D crystals, organic compounds can actually be incorporated into the crystal as 2D phases. Thus, for example, layered Ruddlesden–Popper phases are obtained. We present photoswitchable azobenzene ligands with different head-group lengths for the synthesis of 2D and 3D hybrid perovskite phases. The energy transfer mechanisms are influenced by the length of the molecular spacer moiety, which determines the distance between the π system and the semiconductor surfaces. We find huge differences in the photoswitching behaviour between the free, surface-coordinated and integrated ligands between the perovskite layers. Photoswitching of azobenzene ligands incorporated in 2D phases is nearly quenched, while the same mechanism for surface-coordinating ligands is greatly improved, compared to the free ligands. The improvement originates from an energy transfer from perovskite to azobenzene, which is strongly distance-dependent. This study provides evidence for the photoswitching of azobenzenes as ligands of hybrid perovskites, which depends on the spacing between the chromophore and the perovskite phase.
Keywords: interface design; molecular switches; organic–inorganic hybrid materials; particle synthesis; semiconductors; transport across interfaces